Ancaman rasuah di Perlis: kesedaran awam & peranan SPRM - Hamdah, Nor Halmey (2021)
Corruption is seen as a worrying crime based on the report from Transparency International (TI) on the Corruption Performance Index (CPI). This crime raises some questions as to whether SPRM does not have an effective mechanism mentality of people who still do not care about these symptoms or the existing laws are not heavy and underestimated by people. Corruption can be described as a phenomenon that increasingly needs to be studied in organisational leadership, where it can be seen in various forms and types. Currently, the crime of corruption has undermined people’s trust in its political systems, institutions, and leadership. This study examines whether the level of awareness of the dangers of corruption influencing corrupt behaviour. This study uses qualitative method for implementation. The findings of the study show that most of the respondents involved in this study have a good level of understanding, education, and perception of the problem/crime of corruption. Looking at the level of understanding is better than the level of perception about corruption. However, there are a handful of respondents who do not understand and do not know that the behaviour stated in the study is about the crime of corruption. This is worrying and needs to be given more attention so that those corruption crimes do not continue to increase. The government needs to implement more approaches with people to enable the level of understanding to increase and the crime of corruption to decrease.